DEVELOPMENT OF FISH BODY ORGAN LEARNING MEDIA FOR CLASS V STUDENTS IN ELEMENTARY SCHOOL - Setiyawan, Yogi; Reffiane, Fine; Agustini, Ferina (Jurnal Penelitian Pendidikan IPA, 2019)
This research is conducted by observation that shows that there is still lack of science learning media that explain the organ material in this case is the material of breathing tool of fish. Difficulties of students in understanding the material also become a consideration by researchers to development media board organ tray fish body. This type of research is a research and development method or Research and Development (R & D). The development of fish board tray board boards consists of five stages: (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. From the fifth step is produced media board tray organ organs of fish. The media products of fish body tray board trays are developed and validated by experts. Results The products and materials from two experts showed the percentage score of 90.38% in the "very decent" category, while the teacher's response to media from both primary schools showed 96.6% percentage and 98.3% included in the "very worthy" category and the results The analysis of their student response questionnaires responds with pleasure using the media board tray of fish's organs. Therefore, the media board tray of fish organs is feasible to use and provide a good impact in the process and student learning outcomes. Based on the results of this study suggestions that can be delivered is that the learning media board fish body tray organ for students of grade V primary school can be used by teachers in science study of human and animal organ materials. Teachers can use the instructional media of fish body tray board for grade V students of elementary school in a fun learning for students.Keywords: learning media, SD science